Profitability Performance of Public Sector Banks in India - Saluja, Jyoti; Kaur, Rajinder (Indian Journal of Finance, 2010)
The banking industry, one of the most important instruments of the national development occupies a unique place in a nation's economy. Profit is the main reason for the continued existence of every commercial organization and profitability depicts the relationship of the absolute amount of profit with various other factors. The main source of operating income of a commercial bank are- interest and discount earned, commission, brokerage, income from non banking assets and profit from sale of or dealing with such assets and other receipts. The expenditure broadly consists of - interest paid on deposits and borrowings and non interest cost or charges incurred on staff salary, stationery, rent, law charges, postage, telegram, telephone etc. In this context, some attempts have already been made at individual as well as at the official level and various aspects of commercial banking profitability have been discussed.